The Greater Superficial Petrosal Nerve Schwannoma: A Brief Report - Sarwar, Mohammad; Tripathy, Laxminarayan; Pramanick, Gobinda; Chatterjee, Sanhita (Indian Journal of Neurosurgery, 2023)
Schwannoma of greater superficial petrosal nerve (GSPNS) is a rare tumor of middle cranial fossa. We report a case of GSPNS presenting with twitching of face and eyelid. We describe its characteristic radiological appearance. Total excision of the GSPNS was done through a subtemporal approach with complete relief of symptoms. GSPNS is a rare tumor of middle cranial fossa. Preoperative diagnosis may be misleading. A high index of suspicion is important to make a correct diagnosis and choose an appropriate approach for surgery as it is amenable to complete excision.
Keywords: greater superficial petrosal nerve; GSPN; schwannoma